Customer Satisfaction Analysis on E-Commerce Sites: Quo Vadis The Role of Brand Leadership? - Jainuri; Iskandar, Joni; Amri, Whan Augustin Ainul; Nadeak, Multi; Novitasari, Dewiana (IJOSMAS, 2022)
This study aims to investigate the effect of brand leadership (consisting of the dimensions of quality, value, innovation, and popularity) perceived by consumers of an e-commerce website on customer satisfaction among private college students. The sample of this research was taken from 1026 students using a simple random sampling technique and using SEM (Structural Equation Model) with SmartPLS software version 3.0 as a statistical tool. The results of this study indicate that all dimensions of brand leadership have a positive and significant effect on customer satisfaction. The quality dimension has the most influence to drive customer satisfaction on e-commerce sites. Then followed by the dimensions of value, innovation, and popularity. The study notes that consumers have logical opinions on leading brands even when they are not yet popular. Online reviews and word-of-mouth reviews can be used to increase brand popularity based on the best product quality.